Evaluation of Lead(II) Removal by Carbon Derived from Gingelly Oil Cake - Nagashanmugam, K.B.; Srinivasan, K. (Asian Journal of Chemistry, 2010)
Carbon was derived from gingelly oil cake by thermal activation method and its Pb(II) removal capacity was compared with commercial activated carbon. The effect of experimental parameters such as pH, initial concentration, contact time and adsorbents dosage were studied. The data were fitted with Langmuir, Freundlich and Temkin models to describe the equilibrium isotherms. The kinetic data fitted well with Lagergren pseudo first order and pseudo second order models. The maximum adsorption capacity for Pb(II) calculated from Langmuir isotherm was found to be 105.26 mg/g for thermally activated carbon. R2 values showed that the experimental data fit well with Freundlich isotherm and pseudo second order kinetics. FT-IR analysis was used to obtain information on the nature of possible interaction between adsorbent and metal ions. SEM images confirmed the adsorption of Pb(II) onto thermally activated gingelly oil cake adsorbent through the morphological observation. Thermodynamic study further showed the feasibility and spontaneous nature of the adsorption. The carbon was also tested for the removal of Pb(II) from lead battery synthetic wastewater. Therefore, it has been concluded that carbon derived from gingelly oil cake can be evaluated as an alternative adsorbent to treat wastewater containing Pb(II) ions.